2021
DOI: 10.1371/journal.pone.0256095
|View full text |Cite
|
Sign up to set email alerts
|

Psychological factors and consumer behavior during the COVID-19 pandemic

Abstract: The COVID-19 pandemic is far more than a health crisis: it has unpredictably changed our whole way of life. As suggested by the analysis of economic data on sales, this dramatic scenario has also heavily impacted individuals’ spending levels. To better understand these changes, the present study focused on consumer behavior and its psychological antecedents. Previous studies found that crises differently affect people’s willingness to buy necessities products (i.e., utilitarian shopping) and non-necessities pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
134
3
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(182 citation statements)
references
References 83 publications
(106 reference statements)
3
134
3
6
Order By: Relevance
“…The propensity to share food ordered with the help of applications designed for online distribution was found in the case of close family members or work colleagues and students who live together in dormitories [106]. At the same time, other studies conducted during the COVID-19 pandemic have shown that people with higher education levels tend to buy larger quantities of goods than people who have a lower level of education [11,107]. Young people are individuals with the propensity to use digital applications more and post images of food items on their social networks, a tendency that is amplified in the context of online food delivery application usage [108].…”
Section: Sampling and Data Collectionmentioning
confidence: 97%
See 2 more Smart Citations
“…The propensity to share food ordered with the help of applications designed for online distribution was found in the case of close family members or work colleagues and students who live together in dormitories [106]. At the same time, other studies conducted during the COVID-19 pandemic have shown that people with higher education levels tend to buy larger quantities of goods than people who have a lower level of education [11,107]. Young people are individuals with the propensity to use digital applications more and post images of food items on their social networks, a tendency that is amplified in the context of online food delivery application usage [108].…”
Section: Sampling and Data Collectionmentioning
confidence: 97%
“…Thus, in addition to "classic" variables that define consumer behavior in a traditional way, such as product quality, satisfaction and learning, the situation caused by the pandemic puts particular pressure on consumers and producers/providers alike, with other different variables coming into light, variables capable of measuring factors that are specific to the new types of needs and consumption motivations. Among these, we can cite safety measures-elements found to be very important for retaining customers-and illicit loyaltytype behaviors [10], or variables which are part of a specific group of variables (those of a psychological nature)-fear, anxiety, stress, depression, self-justifications and personality traits [11]. Different authors try to grasp certain features and characteristics of consumers' behavior during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Referring to the data display grouping content in components in Ant Design Vue and existing shopping website applications, we summarized and selected views in the shopping environment as follows: (a) These selection decision biases, affected by the serial position effect, are found to be applicable to many different types of consumer experience [19]. In consumer psychologyrelated research, researchers mostly use a specific task scenario as the basis [18,20,21], combined with the psychological experimental paradigm and consumer application context, to study the influence of the serial position effect on user decision-making bias in this task context. Most of these studies were limited to the comparison of traditional shopping tasks and rarely studied the inducing effect of different forms of information visualization from the perspective of ergonomics.…”
Section: Factors Influencing Online Shopping Decisionsmentioning
confidence: 99%
“…Public health emergencies may adversely affect the mental health of the public ( Di Crosta et al, 2020 , 2021 ; Cannito et al, 2021 ; Chirumbolo et al, 2021 ). This effect can manifest into different results, such as burnout, post-traumatic stress disorder (PTSD, a recurrent mental and physical distress happening after dangerous or catastrophic, transient, or long-lasting situations), anxiety, and depressive symptoms ( Lancee et al, 2008 ; Fontalba-Navas et al, 2017 ; Probst et al, 2020 ; Xu et al, 2020 ; Daniali and Flaten, 2021 ; Wheaton et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%